Health status and household survey of the community served by the White Location clinic in the Knysna municipality - Stanford, Janet Alice (Department of Paediatrics and Child Health, 2023)
The subject of this research is a basic demographic and health status survey. The location of the study is an informal settlement within the Municipality of Knysna, a town on the Southern Cape coast of South Africa with a population of approximately 40 000. Maps in Appendix 1 and 2 show the Western Cape and the study area respectively. The delivery of health services in the area has historically been fragmented, with the private sector and the provincial hospital providing curative services and the Municipality taking responsibility for environmental and personal preventive care such as immunisation and family planning. As a consequence of fragmented health care delivery, health information systems and planning have not been geographically integrated. The philosophy of a cohesive, well planned and equitable service provided to all residents of a district is dependent on adequate information for planning. It is hoped that this study will inform such a planning process.